2002
DOI: 10.2113/gscanmin.40.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pge and PGM in the Bushveld Complex

Abstract: The abundances of the platinum-group elements (PGE), and their relative proportions, are summarized for all the mines exploiting the Merensky Reef on both western and eastern limbs of the Bushveld Complex, in South Africa. Grades for the mined reef interval are uniform over 100 km of strike length, at 5-7 g/t, except for Union mine, where it is currently 8 g/t. The relative proportions of the various PGE are extremely constant over this same distance. In contrast, the platinum-group minerals (PGM) vary enormou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 48 publications
2
33
0
1
Order By: Relevance
“…These studies complemented the extensive literature available (e.g. Alapieti and Lahtinen 1986;Cawthorn et al 2002;Kingston and El-Dosuky 1982;Kinloch 1982;Kinloch and Peyerl 1990;Lee 1996;McLaren and De Villiers 1982;Prichard et al 2004). A wide range of PGM has been reported in various deposits and localities around the world (see Cabri (2002) and references therein for details) and included notably PGE-rich sulfides, tellurides and bismuthotellurides, arsenides, antimonides or alloys.…”
Section: Platinum-group Mineralsmentioning
confidence: 60%
“…These studies complemented the extensive literature available (e.g. Alapieti and Lahtinen 1986;Cawthorn et al 2002;Kingston and El-Dosuky 1982;Kinloch 1982;Kinloch and Peyerl 1990;Lee 1996;McLaren and De Villiers 1982;Prichard et al 2004). A wide range of PGM has been reported in various deposits and localities around the world (see Cabri (2002) and references therein for details) and included notably PGE-rich sulfides, tellurides and bismuthotellurides, arsenides, antimonides or alloys.…”
Section: Platinum-group Mineralsmentioning
confidence: 60%
“…There have been many studies of platinum-group minerals (PGM) in the Bushveld complex, e.g., Cawthorn et al (2002b), Merkle & McKenzie (2002). The PGM assemblage is variable along strike of the Merensky Reef.…”
Section: Pgm In the Merensky Reefmentioning
confidence: 99%
“…Euhedral crystals of PGM constitute the more common texture. Cawthorn et al (2002b) observed that although the PGE content of the Merensky Reef is relatively constant, the minerals that host the PGE vary considerably. In their opinion, this pattern indicates a uniform process of collection and a secondary evolution of the PGM, which varies according to conditions locally in the reef.…”
Section: A Secondary Origin For the Pgmmentioning
confidence: 99%
“…The Merensky reef consists of pegmatoidalmelanorite (70%-90% orthopyroxene) that contains base-metal sulfides and up to four chromite seams confining the pegmatoid layer [45,63,64]. The melanorite is about 10 cm to 30 cm thick, whereas the chromite seams measure 1 cm to 3 cm [45].…”
Section: The Bushveld Complexmentioning
confidence: 99%
“…The occurrence of PGE elements is closely linked to the presence of Fe-Ni-Cu sulfides [44]. The PGE-bearing minerals occur enclosed in base-metal sulfides, along grain boundaries and the contact zones of sulfides and silicates or oxides [44,63]: in 38% to 97% of occurrences, PGE-bearing minerals were found to be enclosed in or attached to base metal sulfides; the remainder are enclosed in silicates [64,66]. The most commonly occurring base metal sulfides are pyrrhotite, pentlandite and chalcopyrite, with~40%,~30% and~15%, respectively [65,66].…”
Section: The Bushveld Complexmentioning
confidence: 99%